Establishing Regional Medical Campuses to Ensure Comparable Experiences: Recommendations From a Narrative Review. (July 2020) - Byerley, Julie S; Foster, Johanna H; Beck Dallaghan, Gary L
Background: Given increasing class sizes and desires to keep costs down, many medical schools are developing regional clinical campuses. We found our regional campus system to be very successful in allowing class size expansion, inspiring a workforce for the state, and concurrently allowing our students to individualize their experience. We desire to articulate our experience, with a review of the relevant evidence, with the goal of assisting other medical schools in their efforts to develop regional medical campuses. Methods: We conducted a narrative literature review to identify considerations for developing regional campuses, taking into consideration our experiences in the process. A medical librarian undertook a literature search for the purposes of this narrative review. Results: Of the 61 articles identified, 14 were included for full-text review. Five facets on branch campus development were identified: relationships, infrastructure, curriculum, recruitment, and accreditation. Within each of these facets we provide further details based on findings from the literature complemented by our experience. Conclusions: Launching a regional campus requires building relationships with clinical partners, ensuring an infrastructure that supports student need and accreditation, comparable curriculum with the same objectives and assessment measures, and aspects of the experience that inspire a student desire to learn in that setting. We share our experience in building successful branch campuses, which have added significantly to our large public school of medicine and its service to our state.